POLITICAL PARTY LEGITIMACY IN THE QUR’AN: A TAFSĪR AḤKĀM ANALYSIS OF INDONESIA’S CONTEMPORARY POLITICAL SYSTEM - Makmunzir Mukhtar; Aban Al-Hafi; Muhammad Nuzul Abraar; Muhammad Ainun Sholeh W. Hasyim (Malikussaleh Social and Political Reviews, 2026)
This study aims to examine the normative legitimacy of political parties from a Qur’anic perspective by analyzing Qur’anic political-ethical principles and their relevance to Indonesia’s party system. Employing a qualitative approach based on library research with a descriptive–analytical design, this study draws primarily on Qur’anic verses related to amānah (trust), justice (‘adl), deliberation (shūrā), amr ma‘rūf nahy munkar (enjoining good and preventing wrongdoing), and social unity (al-waḥdah). These verses are analyzed through classical and contemporary tafsīr aḥkām, particularly the works of al-Ṭabarī, al-Qurṭubī, and ‘Alī aṣ-Ṣābūnī. Data are examined using qualitative content analysis to identify dominant normative themes, trace interpretive patterns, and inductively relate them to the functional roles and institutional practices of political parties within Indonesia’s democratic system. The findings indicate that the Qur’an neither legitimizes nor delegitimizes political parties on the basis of their formal institutional structure, but rather on the extent to which they operationalize Qur’anic ethical principles in the exercise of political power. Accordingly, the normative legitimacy of political parties in the Qur’anic perspective is functional and conditional, contingent upon their commitment to substantive justice, public accountability, deliberative participation, and collective public welfare in governance.